Intellectual Firm: Key Features and Development Models - Sukharev, Oleg Sergeevich (Journal of the knowledge economy, 2023)
The purpose of this study is to identify the comparative characteristics of an intelligent enterprise relative to a production and transaction enterprise, which allows us to identify its dynamics modes for changing the structure of intelligence. The approaches used in the study include the provisions of the modern theory of the firm, the method of taxonomy, and the comparative and structural analysis. An intelligent enterprise is an organization whose subject of activity is intelligence, represented in the form of knowledge, experience, and skills, that is, intelligent capital, as well as abilities, as a special type of knowledge that allows you to process and apply other different types of knowledge. The result of the study can be considered as the identified distinctive features of the functioning of intelligent enterprises, the identified modes of dynamics for changing the components of intelligence, which allowed us to justify four basic models of the development of an intelligent enterprise within the framework of the “knowledge-intelligence” matrix deficit, concentration, inertia, and activism and their respective management strategies. The model of competition of intellectual firms in the institutional plane, that is, according to standards, rules, in which the initiator of institutional changes receives additional benefits from the fact that the competing party is forced to follow the established rules and procedures, is considered. The selected models of the functioning of an intelligent firm allow us to outline a set of management tools in relation to the change in the intelligence of the firm.